Articular Contact Mechanics from an Asymptotic Modeling Perspective: A Review - Argatov, Ivan; Mishuris, Gennady (Frontiers in Bioengineering and Biotechnology, 2016)
In the present paper we review the current state-of-the-art in asymptotic modeling of articular contact. Particular attention has been given to the knee joint contact mechanics with a special emphasis on implications drawn from the asymptotic models, including average characteristics for articular cartilage layer. By listing a number of complicating effects such as transverse anisotropy, nonhomogeneity, variable thickness, nonlinear deformations, shear loading, and bone deformation, which may be accounted for by asymptotic modeling, some unsolved problems and directions for future research are also discussed.